Forced convection for flow across two tandem cylinders with rounded corners in a channel. (March 2019) - Zhang, Wei; Chen, Xiaoping; Yang, Hui; Liang, Hong; Wei, Yikun
Highlights: Forced convection heat transfer of flow past tandem cylinders with rounded corners. Effects of gap ratio and corner radius of the cylinders are studied. Flow is stabilized as the cylinders are rounded at a large corner radius. Steady and unsteady gap flows are observed at small and larger gap ratios. Flow and heat transfer characteristics are determined by the gap flow patterns. Abstract: This work presents the first numerical investigation on the forced convection of flow across two tandem cylinders with rounded corners in a channel at Re  = 100. Both cylinders have the geometry of a square rounded at all corners with a radius of curvature R, which is non-dimensionalized as R +  =  R / D where D is the cylinder diameter, thus the cylinder geometry can be square ( R +  = 0.0), partially rounded ( R +  = 0.1–0.4) or circular ( R +  = 0.5). The two cylinders are separated at a distance in the streamwise direction as characterized by the parameter of gap ratio ( GR ) chosen at GR  = 1(1)8. The objective of this work is to explore the effects of two significant parameters, i.e., gap ratio and corner radius, on the flow unsteadiness and heat transfer characteristics of the tandem arrangement that has not been studied before. The effects of the two parameters are exhibited and analyzed by the instantaneous temperature and vorticity fields, variation of representative aerodynamic and heat transfer quantities, spatial distributions of local heat transfer rate, flow behaviors in the gap and the near-wake regions, and temperature distribution and variation on the channel wall. The results are presented by time-averaged and fluctuating quantities to reflect both mean and pulsating behaviors. We observed that the cylinder geometry determines the unsteadiness of the near-wake flow after the downstream cylinder; the flow is always unsteady for square-like cylinders where the corner radius is small, while the flow can be stabilized by the circular-like cylinders with larger corner radii that the flow fluctuation is greatly weakened or even fully suppressed at small GR s. Numerical results also reveal that the gap flow is steady at small GR s and unsteady at large GR s, as categorized as steady gap flow regime and unsteady gap flow regime . There are drastic variations for the representative characteristic quantities at the critical GR where the gap flow transits from steady to unsteady. The different flow regimes categorized by GR and R + also substantially determine the flow patterns in the gap and near-wake regions, the mean and fluctuating of heat transfer rate on the cylinder surface and the temperature variation on the channel wall.